A minimally manipulated preservation and virus inactivation method for amnion/chorion - Zhang, Shang; Gao, Lichang; Wang, Pin; Ma, Yuyan; Wang, Xiaoliang; Wen, Jie; Cheng, Yu; Liu, Changlin; Zhang, Chunxia; Liu, Changfeng; Yan, Yongli; Zhao, Chengru (Frontiers in Bioengineering and Biotechnology, 2022)
Allogeneic amnion tissues have been widely used in tissue repair and regeneration, especially a remarkable trend of clinical uses in chronic wound repair. The virus inactivation procedures are necessary and required to be verified for the approval of biological products. Cobalt-60 (Co-60) or electron-beam (e-beam) are the common procedures for virus and bacterial reduction but the excessive dose of irradiation was reported to be harmful for biological products. Herein we present a Riboflavin (RB)-Ultraviolet Light (UV) method for virus inactivation of amnion and chorion tissues. We used the standard in vitro limiting dilution assay to test the viral reduction capacity of the RB-UV method on amnion or chorion tissues loaded with four types of model viruses. We found RB-UV was a very effective procedure of inactivating viruses of amnion and chorion tissues, which could be used as a complementary way of Co-60 irradiation. In addition, we also screened the washing solutions and drying methods for the retention of growth factors.